2002
DOI: 10.1038/ni839
|View full text |Cite
|
Sign up to set email alerts
|

A GPI-linked isoform of the IgD receptor regulates resting B cell activation

Abstract: The induction of a humoral response depends upon efficient cross-linking by antigen of surface immunoglobulin on primary B lymphocytes. We demonstrate here the presence of a glycosylphosphatidylinositol-linked isoform of membrane IgD (mIgD) receptors on murine resting B cells. This subset was constitutively localized to cell membrane raft microdomains. Its stimulation resulted in the activation of cAMP-dependent signaling pathways, which integrated with signals derived from the transmembrane mIgD receptors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…H and L chains were detected using rabbit anti-human IgA, anti-human IgD, and anti-human k L chain Abs. The IgD H chain splits up into two distinct bands, which might reflect the full-length transmembrane receptor and a cleaved, GPI-linked form (34,35). Interestingly, only one of the two appears to be cross-linked efficiently to gluten peptide.…”
Section: Discussionmentioning
confidence: 99%
“…H and L chains were detected using rabbit anti-human IgA, anti-human IgD, and anti-human k L chain Abs. The IgD H chain splits up into two distinct bands, which might reflect the full-length transmembrane receptor and a cleaved, GPI-linked form (34,35). Interestingly, only one of the two appears to be cross-linked efficiently to gluten peptide.…”
Section: Discussionmentioning
confidence: 99%
“…The number of known GPIlinked B cell surface Ags is limited (38). Other than CD48, those expressed on B cells include CD24 and CD14, the LPS receptor, and a minor subset of IgD (39). Fig.…”
Section: Induction Of I␥2a Requires the Presence Of Cd48 On B Cellsmentioning
confidence: 99%
“…Potential Ags for IgM a B cells should be no different between 3H9-and 3H9R Tg BWF 1 mice; however, IgM a B cells in 3H9R but not 3H9-Tg BWF 1 mice expressed IgD and could switch V H 3H9 or a different V H generated by editing on the Tg allele to IgG or other constant regions. Recently reported results have indicated that IgD may be important for B cell activation and germinal center formation (37,38). Likewise, signaling through B cell surface IgG is more effective for signaling activation, and consequently, the induction of more clonal expansion than signaling through IgM (39).…”
Section: Anergy In Igm Aϩ B Cells In Conventional 3⌯9-and Knock-in 3hmentioning
confidence: 99%